2022
DOI: 10.5114/ceh.2022.123096
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early bleeding after endoscopic variceal ligation for esophageal varices: a systematic review and meta-analysis

Abstract: Aim of the study: Endoscopic variceal ligation (EVL) is important for emergency as well as prophylactic management of esophageal varices. Early bleeding after EVL is associated with significant morbidity and mortality. Assessing the likelihood of early post-EVL bleeding and its determinants can help deciding therapeutic strategies for high-risk patients. The aim of the present meta-analysis was to identify predictors of early bleeding after EVL. Material and methods: A comprehensive search of the literature wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
(70 reference statements)
0
2
0
1
Order By: Relevance
“…Previous studies have shown that hemoglobin level is an important predictor of early rebleeding after EVL [10,11,22]. As for the impact of blood transfusion on the safety after EVL, this study also further analyzed the impact of RBC transfusion to maintain different postoperative Hb levels (Hb < 70 g/L, 70 g/L ≤ Hb < 90 g/L, and Hb ≥ 90 g/L) on early rebleeding after EVL.…”
Section: Construction Of the Nomogram Prediction Modelmentioning
confidence: 99%
“…Previous studies have shown that hemoglobin level is an important predictor of early rebleeding after EVL [10,11,22]. As for the impact of blood transfusion on the safety after EVL, this study also further analyzed the impact of RBC transfusion to maintain different postoperative Hb levels (Hb < 70 g/L, 70 g/L ≤ Hb < 90 g/L, and Hb ≥ 90 g/L) on early rebleeding after EVL.…”
Section: Construction Of the Nomogram Prediction Modelmentioning
confidence: 99%
“…Метод эндоскопического лигирования вариксов пищевода (ЭЛ ВРВП), в силу своей минимальной инвазивности, на сегодняшний день получил широкое распространение и рекомендован как наиболее предпочтительный [6]. Обратной стороной ЭЛ, негативно влияющей на выживаемость больных после ОПВК, являются специфичные для метода осложнения, среди которых наиболее опасным является постлигатурное кровотечение, прямо зависимое по частоте развития от числа одномоментно установленных лигатур [7]. Раннее (до 12 часов после эпизода ОПВК) эндоскопическое вмешательство ассоциировано с более высокой частотой рецидива кровотечения [8].…”
Section: Introductionunclassified
“…28 A technical note on AI on detection and characterization of colorectal polyp further supplemented the above review by a comprehensive explanation of the concept AI. 29 Other reviews published last year worth mentioning include linear endoscopic ultrasound examination of the biliary system and its clinical applications, 30 capsule endoscopy in inflammatory bowel disease, 31 environmentally sustainable endoscopy practices, 32 efficacy of over-the-scope clips compared to standard therapy for nonvariceal upper gastrointestinal bleeding, 33 gastrointestinal subepithelial lesions, 34 pictorial essay depicting linear endoscopic ultrasound examination of pancreas anatomy, 35 application of endobiliary and pancreatic radiofrequency ablations. 36…”
mentioning
confidence: 99%